Razširjenost navadnega (potočnega) škržka (Unio crassus Philippson, 1788) na Goričkem (SV Slovenija) - Vaupotič, Marjan (Natura Sloveniae, 2009)
The distribution of the endangered species Unio crassus in the Goričko region is presented, based on the results of two methodologically different ways of data collecting. Goričko is one of malacologically underinvestigated regions of Slovenia. Owing to the important role of fishes in this mussel development,a list with fish species that occur in the localities with the mussels is attached.
Keywords: Classification; Ecosystem; Ekosistem; Fresh Water; Goričko; Mussels; potočni škržek; Sladka voda; Slovenia; Slovenija; školjke; Školjke sladkovodne; zoogeografija